Customer satisfaction in the digital era: Evidence from Islamic banking - Ghazi Zouari; Marwa Abdelhedi (Journal of Innovation and Entrepreneurship, 2021)
Purpose: Based upon an extended SERVQUAL model, this paper attempts tocontribute to the Islamic banking literature by examining the impact of digitalization,as a service quality dimension, on customer satisfaction. Design/methodology/approach: Two dimensions, i.e., digitalization andcompliance, are added to the existing SERVQUAL model of five dimensions. Resultsare drawn from a self-completed survey of a convenience sample of 145 TunisianIslamic bank customers for the year 2018. Factor analysis and regression analysis areused to determine factor structure and determine the impact of service qualitydimensions, especially digitalization, on customer satisfaction in Islamic banking. Findings: The factor analysis extracted five dimensions of service quality, i.e.,confidence, compliance, digitalization, tangibles, and human skills. The paperdemonstrates a positive and significant relationship between the main dimensions ofcustomer service quality and customer satisfaction, except for tangibles.Research limitations/implications:Although the outcomes lend support to theextended SERVQUAL model, the results are derived based on a relatively averagesample size in one country (Tunisia). It might also be useful to enlarge the studysample for better generalization of the findings in other countries and include acomparison between Islamic versus conventional banking about service quality andcustomer satisfaction. Moreover, we can applicate another original method for theMeasuring and Implementing Service Quality like the multicriteria method dubbed(MUSA). Managerial implications: To remain competitive, Tunisian Islamic banks need topay attention to the way the services are delivered and not take it for granted thatcustomers are only focusing on compliance. Dealing henceforth with Generation Ycustomers, they must persevere in bringing their customer service into the digitalera. Originality/value: This study is one of the few which tries to investigate the driversof customer satisfaction for Islamic banks in a Digital Era. It reveals that althoughcustomers pay special attention to Sharia laws, the way services are deliveredmatters to them too. From now on, digital banking must appear among the Islamicbank features to stay relevant in the Digital Era.
Keywords: G21; O33; 650; Customer satisfaction; Digital banking; Islamic banks; Service quality; SERVQUAL model; Tunisia